(adsbygoogle = window.adsbygoogle || []).push({}); 1. The problem statement, all variables and given/known data

Verify that the inverse of an automorphism is an automorphism.

2. Relevant equations

3. The attempt at a solution

Let [itex]f:G\to G[/itex] be an automorphism. Then, [itex]f(xy)=f(x)f(y)[/itex] [itex]\forall x,y\in G[/itex].

Then, we define the inverse [itex]f^{-1}:G\to G[/itex] by [itex]f^{-1}(f(x)) = f(f^{-1}(x)) = x[/itex] [itex]\;\;\forall x\in G[/itex]. We get [itex]f^{-1}(f(x)f(y))=f^{-1}(f(xy))=xy=f^{-1}(f(x))f^{-1}(f(y))[/itex]. Since [itex]f^{-1}(f(x)f(y))=f^{-1}(f(x))f^{-1}(f(y))[/itex], [itex]f^{-1}[/itex] is an automorphism.

I was watching http://www.extension.harvard.edu/openlearning/math222/" [Broken], and this came up as an exercise in lecture 3. I was wondering if I did this problem correctly.

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Inverse of Automorphism is an Automorphism

**Physics Forums | Science Articles, Homework Help, Discussion**